The Effect of Work Climate, Job Promotion, and Organizational Culture on the Performance of Batam Authority Employees - Yusuf, Muhammad; Maizar, Maizar (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
The purpose of this study is to analyze the Work Climate, Promotion of Positions, and Organizational Culture on the Employee Performance of Batam Authority partially and simultaneously. This research is quantitative from primary sources collected through questionnaires. The data collection technique is Random Sampling. The data analysis used was instrument testing, which was carried out through validity and reliability testing, while the data analysis technique used was descriptive analysis method and quantitative analysis using multiple linear regression analysis techniques. The results showed that partially the work climate variable was significant in employee performance. The promotion variable had a significant effect on employee performance. Organizational culture variables had a significant effect on employee performance. The results of simultaneous testing of the variables of Work Climate, Promotion of Position, and Organizational Culture had a significant effect on the Employees Performance of Batam Authority.